The Thorium fuel cycle in nuclear reactors (2024)
This thesis explores the potential of thorium-based nuclear fuels in Pressurized Water Reactors (PWRs), focusing on the thorium fuel cycle and its various implementations. The research investigates the benefits and challenges associated with thorium fuel, including its higher conversion ratios, improved thermal properties, and intrinsic proliferation resistance. The study includes detailed simulations using OpenMC to analyze the behavior of thorium oxide (ThOX) with uranium-233 (233 U ) at different concentrations. The results demonstrate that while thorium-based fuels can achieve breeding, maintaining criticality presents challenges. The thesis also examines the impact of fuel composition and concentration on reactor performance and safety. The findings suggest that optimizing these parameters is crucial for enhancing the performance and safety of thorium-based fuels. The research concludes with a discussion on the future prospects of thorium in the nuclear industry and the need for further research and development to fully realize its potential as a sustainable nuclear fuel.